The Poetic Maqama and the Sana’ani Maqama: A Comparative Analytical Study of Narrative Structure and Rhetorical Patterns - Jumaa, Thanaa Ayman (Journal of Arabic Language Sciences and Literature, 2025)
This research aims to study the narrative structure and rhetorical patterns in the poetic Maqama of Badi’ al-Zaman al-Hamadhani and the San’ani Maqama of al-Hariri, through a comparative analytical approach that reveals the similarities and differences between the two texts. The study adopts a descriptive, analytical, and comparative approach, employing the tools of narrative and rhetorical criticism to monitor the mechanisms of textual construction and its stylistic manifestations. The results showed that both maqamat share three main narrative elements: plot, narrator, and character, with differences in the use of rhetorical style and rhetorical techniques, reflecting a difference in the aesthetic and semantic function of each maqamat. I recommended the necessity of expanding the comparison to include other maqamat to reveal the diversity in narrative and rhetorical patterns within the Arab heritage, so that the researcher can apply these maqamat to his environment and the events he experiences.